Learning to Manage Our Futures: The Participative Redesign of Societies in Turbulent TransitionLearning to Manage Our Futures: The Participative Redesign of Societies in Turbulent Transition, by WilliamsTrevor A. New York: John Wiley, 1982, 202 pp., $19.95 cloth. - McCann, Joseph E. (Academy of Management Review, 1984)
The article presents a review of the book ?Learning to Manage Our Futures: The Participative Redesign of Societies in Turbulent Transition,? by Trevor A. Williams.